ANALYSIS EFFECTIVENESS OF THE BAZNAS JEMBER REGENCY RETAIL EMPOWERMENT PROGRAM Z-MART IN IMPROVING THE WELFARE OF MUSTAHIK - Chynthia Putri Danisa Baihaqi; Inayah Swasti Ratih (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
Abstract This study aims to analyze the effectiveness of the Z-Mart Retail Empowerment program in improving the welfare of Mustahik recipients of the Z-Mart Retail Empowerment program of the National Amil Zakat Agency (BAZNAS) of Jember Regency. This study uses a descriptive qualitative approach. The data was obtained through in-depth interviews, field observations, and documentation with informants consisting of the Person in Charge of the Z-Mart BAZNAS Retail Empowerment program in Jember Regency, mustahik business actors, the surrounding community, and consumers. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the Z-Mart Retail Empowerment program is quite effective in improving the welfare of mustahik, This can be seen from the increasing number of customers, as well as the ability of mustahik to meet the economic needs of families. This program also has an impact on the spirit of mustahik in furthering his business. Factors supporting the success of the program include business capital assistance, store branding, training, and mentoring. The obstacles faced include the limitation of companions, coordination of mustahik candidate data, and differences in the level of readiness and responsibility of mustahik to run a business. Therefore, a strategy to strengthen selection, mentoring, and assistance schemes is needed so that the program is sustainable. Keys: Productive Zakat, Z-Mart, retail empowerment, mustahik welfare, BAZNAS Abstrak Penelitian ini bertujuan untuk menganalisis Efektivitas program Pemberdayaan Ritel Z-Mart dalam meningkatkan Kesejateraan Mustahik penerima bantuan program Pemberdayaan Ritel Z-Mart Badan Amil Zakat Nasional (BAZNAS) Kabupaten Jember. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data diperoleh melalui wawancara mendalam, observasi lapangan, dan dokumentasi dengan informan yang terdiri dari Penanggungjawab program Pemberdayaan Ritel Z-Mart BAZNAS Kabupaten Jember, mustahik pelaku usaha, masyarakat sekitar, dan konsumen. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa program Pemberdayaan Ritel Z-Mart tergolong efektif dalam meningkatkan kesejahteean mustahik, Hal ini terlihat dari meningkatnya jumlah pelanggan, serta kemampuan mustahik dalam memenuhi kebutuhan ekonomi keluarga. Program ini juga berdampak pada semangat mustahik dalam melajutkan usahanya. Faktor pendukung keberhasilan program meliputi bantuan modal usaha, branding toko, pelatihan, dan pendampingan. Adapun kendala yang dihadapi antara lain keterbatasan pendamping, koordinasi data calon mustahik, serta perbedaan tingkat kesiapan dan tanggungjawab mustahik menjalankan usaha. Oleh karena itu, diperlukan strategi penguatan seleksi, pendampingan, dan skema bantuan agar program berkelanjutan. Kata kunci: Zakat Produktif, Z-Mart, pemberdayaan ritel, kesejahteraan mustahik, BAZNAS